Strategic Planning Customer Experience using Predictive Analysis Indihome PT Telkom - Achmad, Shandy Asri; Anggina, Pratami; Rudito, Priyantono (Institut Teknologi Sepuluh Nopember, 2020)
Telkom transformation paradigm by Innovating and disrupting the fast-changing industry is the main challenge right now. There is external challenging such as changing customer behavior and high performing Customer Experience (CX) focused industries that seeing customer and business growth. In PT Telkom itself, internal challenges there is a financial performance on a decreasing trend and for Net Promoter Score (NPS) is below best in class benchmark globally. The objective is elevating CX as a corporate strategic priority, engaging all stakeholders to achieve CX transformation. PT Telkom every year doing Net Promoter Score and Net Emotional Value (NEV) to measuring the loyalty of a firm's customer relationships and customer satisfaction that correlated with revenue growth. The author takes the model from secondary data from NPS and NEV Report from 2014 – 2018 of PT Telkom Indonesia, focused in Telkom Regional 3 West Java and assign relationship and satisfaction dimension and attribute. Using predictive analytics is a method that analyzing current and historical facts to make predictions about the future to determine an accurate strategy and can improve customer experience based on the appropriate level of correlation. From NPS and NEV report the dimensions and attributes are processed by predictive analysis using correlation and regression. The fact-finding that based on that analytics will be a strong correlation attributes that would become the key to strategic planning for a customer experience that in a lining with corporate strategy. The strong correlation attribute from this statistical processing is the installation process is long, friendliness of the technician, and ease of accessing points. Then the strategic planning for customer experience is from the result from predictive analytics combine with benchmarking with other telco’s company to propose strategic program end-to-end customer journey and integrated to back end system, digitalization and digital ecosystem will be impacted and gave a result business and revenue.